2017
DOI: 10.3390/land6020024
|View full text |Cite
|
Sign up to set email alerts
|

Governance of Land Use Planning to Reduce Fire Risk to Homes Mediterranean France and California

Abstract: Abstract:Wildfire is a natural part of forested Mediterranean systems. As humans continue to live and build housing in these areas, wildfire is a constant threat to homes and lives. The goal of this paper is to describe aspects of land-use planning that are used to reduce wildfire risk in institutionally divergent regions; southern France and California. By reviewing relevant legislation and planning documents and conducting in person interviews with fire and planning professionals, we identify the institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 41 publications
(45 reference statements)
0
13
0
2
Order By: Relevance
“…For instance, there exists a substantial body of research exploring the adoption of fuels reduction and other property-level mitigations (e.g., building with fire-resistant materials) in the Home Ignition Zone (HIZ)-an area of 100-200 feet from structures that principally influences whether homes can survive wildfire events with little firefighting effort [40][41][42]. Likewise, researchers conducting simulations of residential development and potential wildfire damages frequently call for land-use planning that discourages additional development in areas at high risk for intense fires, or that require existing property owners to retrofit their structures and manage vegetation in ways that reduce the growing need to protect private properties during fire events (see for example [43][44][45]).…”
Section: Community Diversity and Responsibility For Wildfirementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there exists a substantial body of research exploring the adoption of fuels reduction and other property-level mitigations (e.g., building with fire-resistant materials) in the Home Ignition Zone (HIZ)-an area of 100-200 feet from structures that principally influences whether homes can survive wildfire events with little firefighting effort [40][41][42]. Likewise, researchers conducting simulations of residential development and potential wildfire damages frequently call for land-use planning that discourages additional development in areas at high risk for intense fires, or that require existing property owners to retrofit their structures and manage vegetation in ways that reduce the growing need to protect private properties during fire events (see for example [43][44][45]).…”
Section: Community Diversity and Responsibility For Wildfirementioning
confidence: 99%
“…In sum, while there are certain places where robust levels of zoning, taxes, or vegetation management restrictions might advance fire adaptation, the effectiveness and sustainability of those efforts may be restricted to places where they fit the local culture and do not need the level of grassroots support that would be required in other locations [25,44,62]. Both our results and existing work suggest that ordinances, policies, or laws enacted in some locations might be largely ceremonial-their integration into local culture could be a long process or are less likely to occur.…”
Section: Making Sense Of Local Adaptationmentioning
confidence: 99%
“…In [18], the role of land-use planning to reduce wildfire risk was discussed with reference to two distinct Mediterranean fire regimes, namely southern France and California. Kocher et al [18] observed that in France, wildfire risk planning is organized at the national level, while in California, no federal oversight is present.…”
Section: Highlightsmentioning
confidence: 99%
“…In [18], the role of land-use planning to reduce wildfire risk was discussed with reference to two distinct Mediterranean fire regimes, namely southern France and California. Kocher et al [18] observed that in France, wildfire risk planning is organized at the national level, while in California, no federal oversight is present. This comparison of the western United States with southern Europe is of particular importance given a projected increase in fire impacts on humans in both these Mediterranean systems [2].…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation